Sosialisasi Peranan Orang Tua Dalam Mitigasi Learning Loss Pada Anak Di Era Digital - Siregar, Riadi Syafutra; Ghufronuddin, Ghufronuddin; Astutik, Dwi; Parahita, Bagas Narendra; Yuhastina, Yuhastina (Publikasi Pendidikan, 2023)
The purpose of implementing PKM activities is to increase the knowledge and understanding of parents to be wiser in placing their role in mitigating learning loss in children in the digital era, providing an overview of the digital era, its characteristics, causes, impacts and skills to mitigate learning loss and effective learning strategies that can be given to children. It was carried out by outreach to 40 members of the PKK women's group RT 04/RW 06 Dusun Sawahan, Jaten, Karanganyar on July 17, 2022. The implementation of the activities was divided into six stages; Analysis of the problems and needs of parents, initial tests, delivery of material, discussions and questions and answers, and final tests. To deepen the material, participants were given the opportunity to express the problems faced in accompanying children's learning activities in the digital era. The results of this socialization program show an increase in parents' understanding and knowledge regarding mitigating learning loss in the digital era and fostering the enthusiasm of parents to participate in assisting children so that they are not affected by learning loss and trying to apply it in accompanying children's learning activities